Synchronous Germinal Center Onset Impacts the Efficiency of Antibody Responses - Arulraj, Theinmozhi; Binder, Sebastian C.; Robert, Philippe A.; Meyer-Hermann, Michael (Frontiers in Immunology, 2019)
The germinal centre reaction is an important target for modulating antibody responses. Antibody production from germinal centres is regulated by a negative feedback mechanism termed antibody feedback. By imposing antibody feedback, germinal centres can interact and regulate the output of other germinal centres. Using an agent-based model of the germinal centre reaction, we studied the impact of antibody feedback on kinetics and efficiency of a germinal centre. Our simulations predict that high feedback of antibodies from germinal centres reduces the production of plasma cells and subsequently the efficiency of the germinal centre reaction by promoting earlier termination. Affinity maturation is only weakly improved by increased antibody feedback and ultimately interrupted because of premature termination of the reaction. The model predicts that the asynchronous onset and changes in number of germinal centres could alter the efficiency of antibody response due to changes in feedback by soluble antibodies. Consequently, late initialized germinal centres have a compromised output due to higher antibody feedback from the germinal centres formed earlier. The results demonstrate potential effects of germinal centre intercommunication and highlight the importance of understanding germinal centre interactions for optimizing the antibody response, in particular, in the elderly and in the context of vaccination.